Kecerdasan Buatan dengan Metode ID3 Finite State Machine dalam Turn-Based Tactics Game - Adam Putra Sulaiman; Liliana Liliana; Leo Willyanto Santoso (Jurnal Infra, 2021)
As the world of video game grown and advances there are evenmore those who likes and play them as well. One way to increaseimmersion within video games is by implementing AI (ArtificialIntelligence). AI is an ability within a program or machine thatcan grant said machine/program a power of “thought” so thatthey can do a command without unnecessary human inputs. AndAI had grown constantly significant since the day it wasconceived.However one of AI’s greatest weakness is if implemented toosimplistic within it’s execution, then when someone manage todecode the AI’s pattern, then said player can use this knowledgefor their advantage. And as a consequence, costed the gameimmersion since the game is played not the way it was intended toor become way too easy. To solve said problem, requires aflexible AI that can adapt to the gameplay. Using ID3 decisiontree, AI are expected to be able to using the variable within aTurn-Based Strategy Game to use different options according tothe data it earn. And hopefully with little improvements, thismethod can be used to differing video game genres as well.The test result proven that while ID3 does give some influence forthe AI decision making, during the test run for Turn-Based Gameshown that the Adaptive AI that always chooses the best option ifplayed the same had a WDL overalls (Win-Draw-Lose) of 1:2:0,while Adaptive AI with the ID3 formula and dynamic decisionmaking had a more balanced results of 1:1:1 and random AIalways ended at a disadvantage with 0:0:3. These tests provedthat Adaptive AI provide the most challenge to the player doesn’thave any influence for the early parts of the game. And that theID3 impact were non-existent during the early game butimproving as the game goes on and the data table more varied.